Editorial: Bioethics advances as the foundation of medical work - da Silva Gallo, José Hiran (2024)
In this issue, Revista Bioética brings studies and approaches on subjects such as spirituality and pain, palliative care, social death, communication of bad news in the context of children, medical empathy, suicide and oncological practices.These themes permeate medical practice and impact the lives of patients in the evolution of health, providing continuous transformation and expanding the bioethical vision for humanity.